Deforestation on the Dynamics and Challenges of Forest Area Use and Utilization in Jambi Province - Oktaviana, Shinta; Yulistian, Saldi; Habibie , Syahidullah; Rizal, Randy; Gistala, Brama Nalendra; Badariah, Badariah (BUMI: International Journal of Environmental Reviews, 2025)
Jambi Province is one of the provinces on the island of Sumatra that has a fairly large forest area and serves as an oxygen contributor on the earth's surface. However, the high amount of illegal logging, forest fires, and the expansion of plantation areas and settlements have caused a decrease in forest area, known as deforestation. The most severe deforestation in Jambi Province occurs in Muaro Jambi Regency. In this regency, there are production forest areas and protected forest areas that also experience gradual deforestation every year. Deforestation, if left continuously, will result in increasingly severe forest damage, global climate change, and threaten native animals in the forest. Through the DPSIR (drivers, pressures, states, impacts, and responses) model approach to capture the dynamics of forest area management and utilization in Jambi Province, recommendations and strategies are obtained to address the deforestation problem comprehensively and systematically.